Shaping Eyeballs by Scleral Collagen Cross-Linking: A Hypothesis for Myopia Treatment - Wang, Mengmeng; Corpuz, Christine Carole C.; Zhang, Fengju (Frontiers in Medicine, 2021)
The global prevalence of myopia has brought to the attention of the different eye and vision specialists, who make way to control its progression. Evidence have shown that a proactive reshaping of the eyeball is the core point of myopia developing process, which particularly includes the weakening, thinning and expanding of the sclera. Thus, the sclera is considered to be a prime target for therapeutic manipulation in halting progressive myopia. In the past decades, corneal collagen cross-linking has been applied in clinical practice for treating aberrant corneal remodeling diseases. In this article, we hypothesize that scleral collagen cross-linking (SXL) has a huge potential in stabilizing myopic process by shaping the eyeball and preventing the aberrant scleral remodeling. In contrast with the current methods of optometry correction, such as physiotherapy, pharmacotherapy, spectacles, contact lenses, refractive surgeries, etc., eyeball-shaping method using SXL is a fundamental intervention which aim at the pathogenesis of progressive visual loss of myopia. Compared with the current posterior scleral reinforcement, the most advantage of SXL is that there is no allotransplant into the myopic eye, which means less expenditure, lower risk, and easier to handle in operating.